2009
DOI: 10.1111/j.1742-7843.2008.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amburoside A and Isokaempferide, Polyphenols from Amburana cearensis, on Rodent Inflammatory Processes and Myeloperoxidase Activity in Human Neutrophils

Abstract: The present study evaluated the anti-inflammatory activity of amburoside A (a phenol glucoside) and isokaempferide (a flavonol) isolated from the trunk bark of Amburana cearensis, a medicinal plant used in northeast Brazil for the treatment of asthma. Animals (male Wistar rats or Swiss mice) pre-treated with amburoside A (25 and 50 mg/kg) or isokaempferide (12.5, 25 and 50 mg/kg), orally or intraperitoneally, showed a significant inhibition of the paw oedema induced by carrageenan (1%), prostaglandin E(2) (30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
2
12
0
4
Order By: Relevance
“…P. amboinicus no estudo de apresentou atividade antimicrobiana, sendo eficaz contra enfermidades que acometem o sistema respiratório (garganta inflamada). Em relação à espécie nativa dentro desta categoria, A. cearensis, endêmica do ecossistema de caatinga, foi citada para o tratamento de gripe e inflamações, o que coincide com o estudo de Leal et al, (2008), no qual demonstra que a casca do caule desta espécie tem atividade broncodilatadora e anti-inflamatória. Doenças de Pele e do Tecido Celular Subcutâneo (DPTCS) estiveram relacionadas com a espécie Ziziphus joazeiro sendo a mais utilizada para caspa e tratamento capilar.…”
Section: Concordância De Uso Das Espécies Medicinaisunclassified
“…P. amboinicus no estudo de apresentou atividade antimicrobiana, sendo eficaz contra enfermidades que acometem o sistema respiratório (garganta inflamada). Em relação à espécie nativa dentro desta categoria, A. cearensis, endêmica do ecossistema de caatinga, foi citada para o tratamento de gripe e inflamações, o que coincide com o estudo de Leal et al, (2008), no qual demonstra que a casca do caule desta espécie tem atividade broncodilatadora e anti-inflamatória. Doenças de Pele e do Tecido Celular Subcutâneo (DPTCS) estiveram relacionadas com a espécie Ziziphus joazeiro sendo a mais utilizada para caspa e tratamento capilar.…”
Section: Concordância De Uso Das Espécies Medicinaisunclassified
“…A. cearensis was the most frequently cited plant in two other studies conducted in Rio Grande do Norte State (Roque et al, 2010;Silva & Freire 2010). This species has anti-inflammatory, muscle relaxant and antioxidant (Leal et al, 2009), which explains at least in part the traditional use of A. cearensis in the treatment of respiratory diseases where the pathophysiological characteristics include inflammation, oxidative stress and bronchoconstriction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies reported antinociceptive and antioxidant properties of the hydroalcoholic extract and chemical constituents of this plant (Leal et al, 2009;Leal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory effects can be explained, at least in part, by the ability of these compounds to reduce neutrophil degranulation, myeloperoxidase activity, as well as TNF-alpha secretion (Leal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%